Impacts of dietary supplementation of pyocyanin powder on growth performance, carcase traits, blood chemistry, meat quality and gut microbial activity of broilers - Elwy A. Ashour; Reem M. Farsi; Bothaina A. Alaidaroos; Abdel-Moneim E. Abdel-Moneim; Mohamed T. El-Saadony; Ali O. Osman; Eman T. Abou Sayed-Ahmed; Najah M. Albaqami; Manal E. Shafi; Ayman E. Taha; Mohamed E. Abd El-Hack (Italian Journal of Animal Science, 2021)
Natural antioxidants play an important role in maintaining and improving poultry’s well-being, survival and productive and reproductive performance. Pyocyanin, a secondary blue redox-active metabolite, is one of these natural antioxidants that exert several biological activities to improve birds’ performance. This study estimated the effect of dietary supplementation with pyocyanin powder (PP) on broiler’s growth, carcase and serum properties, meat quality and microbial load activity. A total of 180 1-week-old unsexed chicks were randomly allocated into three groups. The first group served as a control (C) and fed the basal diet, while the second and third groups (P75 and P150) were fed the basal diet supplemented with 75.0 and 150.0 mg PP/kg, respectively. Results showed that overall body weight gain (BWG) was improved (p<.05) in P75 compared to P150 and control groups. Feed intake and feed conversion ratio (FCR) of chicks fed the diet containing PP levels were not altered during all experimental periods compared to the control. Dietary treatments did not affect all carcase traits, blood biochemical parameters and meat sensory characteristics at five weeks of age. Antioxidative status was improved by pyocyanin supplementation as serum malondialdehyde (MDA) was reduced while GST and GSH levels were elevated in P75 and P150 compared to the control. Dietary PP supplements increased (p<.05) the pH, lightness and redness of pectoralis major muscle and reduced (p<.05) the yellowness of the muscle and its contents of thiobarbituric acid and total volatile basic nitrogen. The PP addition showed antibacterial and antifungal activities against several pathogenic bacteria and mycotoxigenic fungi. It could be concluded that pyocyanin can be introduced as a natural, functional and phytogenic feed additive to boost broiler’s growth, improve their meat quality, produce nutritious meat products and reduce pathogenic bacteria without adverse impacts on their productivity.Highlights This work investigated the effect of pyocyanin powder on broiler chickens. The addition of pyocyanin at 75.0 mg/kg diet improved Body weight gain (BWG) and meat quality characteristics. Pyocyanin exerted antibacterial and antifungal activity against several pathogenic bacteria. Pyocyanin could be used as a natural and functional additive to poultry diets.